2015
DOI: 10.1209/0295-5075/111/19001
|View full text |Cite
|
Sign up to set email alerts
|

Information theory approach to the Landers aftershock sequence

Abstract: The study of seismicity is becoming increasingly important with recent disasters such as the Gorkha event in Nepal in 2015. Our models mostly depend on the information given by a seismic catalog, such as rates of events and magnitudes. It has also been shown that seismicity presents long-range correlations. Here, we think about how they should be introduced in our models. We divide the region into cells and represent their activity as a time series. We then calculate how much information one cell has about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The mutual information represents the amount of information that one random variable has about another random variable, accounting for nonlinear correlations as well. This interpretation has been used in text analysis [32], computer vision [33], earthquakes [34], or psychology [35], for example. In the calculations, we divide the probability distributions into 10 intervals, because we found that this number of intervals satisfies the condition to find a robust estimator [36].…”
Section: Discussionmentioning
confidence: 99%
“…The mutual information represents the amount of information that one random variable has about another random variable, accounting for nonlinear correlations as well. This interpretation has been used in text analysis [32], computer vision [33], earthquakes [34], or psychology [35], for example. In the calculations, we divide the probability distributions into 10 intervals, because we found that this number of intervals satisfies the condition to find a robust estimator [36].…”
Section: Discussionmentioning
confidence: 99%